The dialectic of the relationship between the novel and the cinematic text in Ahmed Murad's The Blue Elephant: A critical view (Al-Academy, 2025)
The study examines the dialectical relationship between the novel text and the Blue Elephant cinematic film through a critical vision, using a comparative analytical approach to identify the most important dialectical points and work to analyze and criticize them. The study reached several results, most notably that the dialectical differences that were read and noted are that the cinematic film focused in its details on feelings and emotions, while what we can read in the novel text is that the narrative and accurate description of events took the largest part of the story, the novel of the blue film was characterized by narrative influences, which worked to enrich the literary text and evaluate it, such as: The presence of an overlap between reality and fiction; the overlap between times and worlds that the reader and viewer can observe, which enhances its value. The Blue Elephant used audio and visual effects and employed them in more than one scene. The visual effects were characterized by their quality and perfection, and contributed to the storytelling of the film and were used in places that facilitated the brevity of the dialogue and the accurate description of the scenes and the psychological state of the character, and the decoration and furniture used played an important role in artistic creativity, as did the lighting, colours, camera angles, and shot size that enhanced the aspects of mystery and horror that form the plot of the film